KEPEMIMPINAN BERTUMBUH (STUDI KASUS KEPEMIMPINAN REKTOR UNNES) - Kuswantoro, Agung; Ismiyati, Ismiyati; Purasari, Netty (FEB Universitas Sam Ratulangi Manado, 2019)
The purpose of this research is (1) to know the meaning of leadership grows (2) to know the character that is in the growing leadership (3) To know the theory used in the growing leadership. The type of research used in this study is qualitative research. The technique of determining the informant using purposive sampling (subject to purpose). The meaning of leadership grows refers to the tree philosophy. The tree (1) Cultivates leadership, (2) Strengthening the Leadership Tree, (3) arranging a network of leadership trees, (4) strong trees face storms, and (5) spray the new leadership shoots. The character in the growing leadership was to cultivate leadership seeds, which included understanding humanity and leadership. The theory used in the growing leadership is the theory of behaviour. The suggestion in this study was (1) the need for stronger theoretical support in the growth of leadership. (2) The institution or organization is suitable/appropriate to use this theory in the present time, because it is in accordance with the condition of society. Above, leadership grew based on the experience of a leader.